PARTICIPATORY MANAGEMENT IN IMPROVING COMMUNITY WELFARE IN PEMATANG SERAI VILLAGE - Daulay, Muhamad Toyib; Sanny, Annisa; Sari, Wahyu Indah; Riwanda, Febby (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study analyzes the role of participatory management in improving community welfare in Pematang Serai Village. Through a qualitative approach with in-depth interviews, this study found that community participation in the decision-making process and implementation of local development programs contributed significantly to improving welfare. Such participation builds community belonging, involvement, and capacity, and strengthens relationships between village government and communities. However, challenges faced include lack of awareness, cultural and structural barriers, and limited resources. Recommendations were given to strengthen community capacity, increase understanding of the benefits of participation, and strengthen cooperation between village government and communities. This research provides guidance for policymakers in designing inclusive, participatory, and sustainable development programs.